A leadership-based framework for improving Saudi Arabian female participation in sports - Alruwaili, Mamdouh Dawish (Frontiers in Sports and Active Living, 2023)
Study purpose To analyze the relationship between the leadership styles and sports engagement among female sport persons in Saudi Arabia and proposes a framework model for improving Saudi Arabian female participation in sports. Methods This study adopted an online cross-sectional survey design for achieving the research aim. Survey instruments included multi-factor leadership questionnaire (MLQ) and Utrecht Work Engagement Scale (UWES). The study participants included adult female sports persons from various sports clubs in Saudi Arabia. A total of 329 responses were received, out of which 35 were incomplete; therefore, a total of 294 responses were considered for the data analysis. Results Transformational leadership style was identified to be the most preferred style compared to transactional and laissez-fare leadership styles. Older participants (>25 years) perceived transformational leadership scales including inspirational motivation, intellectual stimulation, and individual consideration to be more effective (p < 0.05) compared to younger participants. Transformational leadership has strong positive correlation with all engagement scales (as correlation coefficient “r” was greater than 0.7, p < 0.01). Conclusion Inspirational motivation could be an effective approach in increasing the female participation in Saudi Arabia, as they are mentally unprepared due to the experience of socio-cultural restrictions for decades.